The Influence of Agile Leadership and Talent Management on Employee Performance Mediated by Workforce Agility - Prasetiawan, Tira; Nurhayati, Mafizatun; Riana, Kurnia Endah (ADPEBI Publisher, 2025)
This study aims to analyze the effect of agile leadership and talent management on employee performance mediated by workforce agility at the Sendang Kamulyan Regional Drinking Water Company, Batang Regency. The sample of this study was permanent staff level employees of the Sendang Kamulyan Regional Drinking Water Company, Batang Regency, totaling 149 employees. The analysis method used in this study is SEM-PLS (Structural Equation Modeling-Partial Least Square). The results showed that agile leadership had no effect on employee performance. Agile leadership had a positive and significant effect on workforce agility. Workforce agility had a positive and significant effect on employee performance. Talent management had a positive and significant effect on employee performance. Talent management had no effect on workforce agility. Workforce agility played a full mediation role between agile leadership and employee performance. Workforce agility only played a partial mediation role between talent management and employee performance.